Reaksi Pasar terhadap Pengumuman Dividen: Studi Empiris Di Bursa Efek Jakarta - sudarto sudarto (Media Riset Bisnis & Manajemen, 2007)
The aim of the research are to examine market reaction and rationality of investor in decision making which is caused by increasing dividend annaoucement in the jakarta stock Exchange. In an efficient market, the current price of the stocks have reflected public information so none of investor is able to afford an abnormal return. The findings are significant affects negative by market reaction and irrational reaction appeared on the stocks. However, the stocks without growth are responded rationally.